1992
DOI: 10.1073/pnas.89.21.10292
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Epstein-Barr virus-encoded RNAs EBER-1 and EBER-2 in interphase and mitotic Burkitt lymphoma cells.

Abstract: The subcellular distribution of the small Epstein-Barr virus-encoded RNAs EBER-1 and EBER-2 has been investigated by using a high-resolution in situ hybridization technique. The distribution prns in Raji cells of fluorescent oligodeoxynucleotides complementary to each RNA were detected by confocal laser nning microscopy. Both RNAs were found in the cytoplasm as well as in the nuclei of interphase cells. In contrast, use of the same technique indicated an exclusively nuclear location for cellular U2 RNA. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 32 publications
1
36
0
2
Order By: Relevance
“…PKR is predominantly found in the cytoplasm, where it is closely associated with ribosomes (46,47). However, electron micrograph analysis and immunogold labeling has also indicated that a fraction of PKR resides in the nucleus (48,49).…”
Section: Isolation and Identification Of Nfar-1 And -2-mentioning
confidence: 99%
“…PKR is predominantly found in the cytoplasm, where it is closely associated with ribosomes (46,47). However, electron micrograph analysis and immunogold labeling has also indicated that a fraction of PKR resides in the nucleus (48,49).…”
Section: Isolation and Identification Of Nfar-1 And -2-mentioning
confidence: 99%
“…The cytoplasm distribution of the EBERs was similar to that of the double-stranded RNA-dependent protein kinase, to which these RNAs could bind, and the location was coincident with the rough endoplasmic reticulum. Thus a cytoplasmic location for EBER-1 and EBER-2 in interphase cells is consistent with the evidence for a role for these small RNAs in translational control (Schwemmle et al, 1992). Despite this sole publication in accord with the potential function of EBERs involved RNP complexes, a recent report (Fok et al, 2006) indicated that EBERs are confined to the nucleus.…”
Section: Localization and Potential Function Of Ebers Involved Rnp Comentioning
confidence: 61%
“…Although one report has suggested that the EBERs have a nuclear location (Howe & Steitz, 1986) more recent in situ hybridization studies (Schwemmle et al, 1992) have indicated that a substantial fraction of both R N A s is found in the cytoplasm. Our experiments did not address the question of whether the EBERs in the nucleus behave similarly to the cytoplasmic EBERs with respect to stabil!ty or post-transcriptional modification.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier in situ hybridization studies suggested that the EBERs may be localized predominantly in the cell nucleus (Howe & Steitz, 1986). However, the EBERs were originally identified as being associated with polysomes (Rymo, 1979) and recently high resolution confocal laser scanning microscopy has produced unambiguous evidence for the presence of both the EBERs in the cytoplasm of Raji Burkitt's lymphoma cells (Schwemmle et al, 1992). The latter finding is consistent with biochemical and genetic evidence that EBER-1 and EBER-2 may have a role in translational control.…”
Section: Introductionmentioning
confidence: 99%